2007
DOI: 10.1038/bdj.2007.944
|View full text |Cite
|
Sign up to set email alerts
|

A survey of denture identification marking within the United Kingdom

Abstract: • Identification marking of dentures is regulated by guidelines in several other countries.• Within the UK, there are no specific guidelines or policies for civilian denture identifi ca tion marking.• The prevalence of denture marking in the UK is low.• The overwhelming opinion of prosthodontic specialists within the UK supports the philosophy of denture marking as a routine procedure.A survey of denture identifi cation marking within the United Kingdom Aim To assess the attitudes of healthcare workers within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
0
17
1
4
Order By: Relevance
“…This study also revealed that in six major dental laboratories marking was performed on 90-100% of complete dentures. Although the extent of denture marking was significantly greater than that found by Murray et al 3 the level of marking in this Scandinavian study demonstrated that over 50% of dentures were unmarked. In a very large study comprising of 1,715 residents from nursing homes in Sweden, the frequency of marked complete dentures evaluated by a screening examination revealed only 35% of the 1,215 dentures among the 1,715 residents were marked.…”
Section: Comparison Between Uk and Other Countriescontrasting
confidence: 82%
See 4 more Smart Citations
“…This study also revealed that in six major dental laboratories marking was performed on 90-100% of complete dentures. Although the extent of denture marking was significantly greater than that found by Murray et al 3 the level of marking in this Scandinavian study demonstrated that over 50% of dentures were unmarked. In a very large study comprising of 1,715 residents from nursing homes in Sweden, the frequency of marked complete dentures evaluated by a screening examination revealed only 35% of the 1,215 dentures among the 1,715 residents were marked.…”
Section: Comparison Between Uk and Other Countriescontrasting
confidence: 82%
“…6.8% of dentures were marked and for the same year in Scotland 3.75% dentures were marked. 3 At that stage the NHS were remunerating dentists using a fee per item scale so an additional fee was available for a permanent patient identification marker in a denture.…”
Section: Patient Awareness Of and Attitude To Denture Markingmentioning
confidence: 99%
See 3 more Smart Citations